1999
DOI: 10.1111/j.1469-7793.1999.00079.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of a Na+–phosphate cotransporter (NaPi‐II) from zebrafish and identification of related transcripts

Abstract: Homeostasis of inorganic phosphate (Pé) in vertebrates is achieved by intestinal absorption and tightly controlled renal excretion (Danisi & Murer, 1991;Berndt & Knox, 1992). A protein family of Na¤-dependent phosphate cotransporters, denoted NaPé-II, is crucially involved in both steps Werner et al. 1998). The expression of NaPé-IIrelated transcripts has been demonstrated in kidney, brain and bone of different species (Hisano et al. 1997;Gupta et al. 1997). Only recently, the cloning of a second isoform, deno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
54
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 35 publications
7
54
1
Order By: Relevance
“…Moreover, 32 P uptake rates are independent of membrane potential ( Forster, Wagner et al 1997;Forster, Hernando et al 1998;Nalbant, Boehmer et al 1999; 12 Segawa, Kaneko et al 2002;Graham, Nalbant et al 2003;Forster, Virkki et al 2006;Ghezzi, Murer et al 2009)). The apparent affinity constants for total P i (K 0.5 Pi ) are typically <100 µM (pH 7.4 and [Na + ] =100 mM), with the exception of (i) a zebra fish isoform (NaPi-IIb1) (K 0.5 Pi =250 µM) (Graham, Nalbant et al 2003), and (ii) the murine and rat NaPi-IIb that exhibit exceptionally high apparent P i affinities (K 0.5 Pi ≈10 µM) (Forster, Villa-Bellosta&Sorribas 2008).…”
Section: Transport Kinetics a Steady-state Transport Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, 32 P uptake rates are independent of membrane potential ( Forster, Wagner et al 1997;Forster, Hernando et al 1998;Nalbant, Boehmer et al 1999; 12 Segawa, Kaneko et al 2002;Graham, Nalbant et al 2003;Forster, Virkki et al 2006;Ghezzi, Murer et al 2009)). The apparent affinity constants for total P i (K 0.5 Pi ) are typically <100 µM (pH 7.4 and [Na + ] =100 mM), with the exception of (i) a zebra fish isoform (NaPi-IIb1) (K 0.5 Pi =250 µM) (Graham, Nalbant et al 2003), and (ii) the murine and rat NaPi-IIb that exhibit exceptionally high apparent P i affinities (K 0.5 Pi ≈10 µM) (Forster, Villa-Bellosta&Sorribas 2008).…”
Section: Transport Kinetics a Steady-state Transport Propertiesmentioning
confidence: 99%
“…However, based on more recent studies and subsequent cloning of other SLC34 isoforms, it is unlikely that this motif represents the only proton interacting site in NaPi-IIa for several reasons. First, although the REK motif is conserved among all NaPi-IIa that display a strong pH dependence (Busch, Waldegger et al 1994;Busch, Wagner et al 1995;Hartmann, Wagner et al 1995;Forster, Hernando et al 1998;Forster, Biber et al 2000), it is present neither in the Zebra fish NaPiIIb1 (Nalbant, Boehmer et al 1999), nor NaPi-IIc, both of which show the phenotypically strong NaPi-IIa pH dependency (Segawa, Kaneko et al 2002). Second, in the flounder NaPiIIb that shows strong pH dependence (Forster, Biber et al 2000) and the zebra fish NaPi-IIb2, that shows weaker pH dependence (Graham, Nalbant et al 2003), the arginine is replaced by a neutral alanine.…”
Section: Proton Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our second strategy involved making a multiple sequence alignment of four currently available mammalian NaPi-IIc sequences and 17 sequences of NaPi-IIa as well as NaPi-IIb isoforms, several of which mediate P i -dependent electrogenic activity when expressed in oocytes (3,(16)(17)(18)(19). The alignment showed that, among the 21 sequences (excluding the N and C termini and ECL-2, where large variations are observed between isoforms), Ϸ75% of residues were 100% identical or in a few cases involved conservative substitutions (Fig.…”
Section: Sequence Alignment Reveals Altered Polarity and Charge Of Rementioning
confidence: 99%
“…Our group has reported the identification of antisense RNAs related to the epithelial Na/phosphate cotransporter from zebrafish, mice and flounder. 21,59,60 The transporter, denoted NaPi-II, is instrumental in maintaining phosphate homeostasis in vertebrates. 61,62 The antisense transcripts from zebrafish have been cloned and extensively characterized, the mouse homologue(s) has just recently been detected by PCR and sequenced.…”
Section: Myosin Heavy Chain (Mhc)mentioning
confidence: 99%